Influence of the energy parameters of the primary circuit on the current characteristics of the DIN-2K accelerator - Vinnikov, D.V.; Katrechko, V.V.; Ozerov, O.M.; Tkachev, V.I.; Marchenko, S.V.; Yuferov, V.B.; Manuilenko, O.V. (Problems of Atomic Science and Technology, 2023)
Optimal voltage values were established for plasma guns and the pulsed current generator providing maximum break current values. The current values were determined for the plasma jumper formation region. The optimal time delay between the triggering of the plasma guns and the pulsed current generator has been established. The beam current was measured in the region behind the vacuum diode and in the plasma jumper region. The ultimate current was determined for the available plant geometry. Встановлено оптимальні значення напруги для плазмових гармат і генератора імпульсного струму, що забезпечують максимальні значення струму розриву. Значення струму визначено для області формування плазмової перемички. Встановлено оптимальну затримку часу між спрацьовуванням плазмових гармат і генератора імпульсного струму. Струм пучка вимірювався в області за вакуумним діодом і в області плазмової перемички. Граничний струм був визначений для наявної геометрії установки.